A review on the trend of physical learning environments and recommendations for future design approach / Nur Syazadiyanah Suraini and Nor Fadzila Aziz - Suraini, Nur Syazadiyanah; Aziz, Nor Fadzila (Universiti Teknologi MARA, Perak, 2023)
For the past three decades, there is an abundance of studies that justified the impact of physical learning space on the student’s learning experience focusing on independent design theories of lighting, acoustic and ventilation among many others. On top of that, a well-designed learning space is also characterised with the vital role to enhance the teaching and learning experience. This paper aims to present a synthesis of over 20 studies from 1990-2021 that focused on the relationship between the physical learning space and users’ experience. The aspects taken are the said criteria of a well-designed learning environment as well as the recommendation for future consideration in designing a learning space. In summary, a physical learning space is not limited to technical and aesthetics nor short-term pedagogical function, but should consider its impact on the expected student outcomes in-line with the evolving trends of education in general. Apart from that, it is also mentioned with an immense importance to include various stakeholders, especially the users in designing effective future learning spaces due to the excessive cost that may incur.